2012
DOI: 10.4049/jimmunol.1103829
|View full text |Cite
|
Sign up to set email alerts
|

Stomatin-like Protein 2 Deficiency in T Cells Is Associated with Altered Mitochondrial Respiration and Defective CD4+ T Cell Responses

Abstract: Stomatin-like protein 2 (SLP-2) is a mostly mitochondrial protein that regulates mitochondrial biogenesis and function and modulates T cell activation. To determine the mechanism of action of SLP-2, we generated T cell-specific SLP-2–deficient mice. These mice had normal numbers of thymocytes and T cells in the periphery. However, conventional SLP-2–deficient T cells had a posttranscriptional defect in IL-2 production in response to TCR ligation, and this translated into reduced CD4+ T cell responses. SLP-2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 61 publications
2
53
0
Order By: Relevance
“…We have previously shown that SLP-2 binds the mitochondrial phospholipid cardiolipin and interacts with prohibitin-1 (PHB1) and PHB2, which are proposed to form specialized cardiolipin-enriched microdomains in the mitochondrial inner membrane important for optimal respiratory function (5,6). Indeed, we showed that deletion of Slp-2 results in decreased cardiolipin microdomains and increased mitochondrial respiration uncoupled from ATP synthase activity, a defect overcome by an increased reliance on glycolysis (5).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…We have previously shown that SLP-2 binds the mitochondrial phospholipid cardiolipin and interacts with prohibitin-1 (PHB1) and PHB2, which are proposed to form specialized cardiolipin-enriched microdomains in the mitochondrial inner membrane important for optimal respiratory function (5,6). Indeed, we showed that deletion of Slp-2 results in decreased cardiolipin microdomains and increased mitochondrial respiration uncoupled from ATP synthase activity, a defect overcome by an increased reliance on glycolysis (5).…”
mentioning
confidence: 88%
“…The oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) were measured with an XF-24 analyzer (Seahorse Bioscience, North Billerica, MA) as described previously (5). Briefly, following stimulation for 48 h, WT and SLP-2 T-K/O T cells were suspended in Seahorse XF assay medium supplemented with 2 mM L-glutamine, 2 mM sodium pyruvate, and 25 mM glucose or galactose and seeded onto XF24 V7 24-well cell culture plates coated with 50 g/ml poly-D-lysine at 500,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…likely to interact with the Ror2 (for required for mlo resistance 2) syntaxin engaged in vesicle-to-target membrane fusions during pathogen-induced transcytosis; (2) for an armadillo-repeat (ARM) protein representing a partial copy of a U-box/ARM E3 ubiquitin ligase (Rnr5); (3) for the cellulose-synthase like protein Hv-CslD2 that appears to be involved in cell-wall based defense (Rnr6); and (4) for a stomatin-like protein 2 (SLP-2)-related protein (Rnr10) involved in stress-induced mitochondrial hyperfusion, touch sensation, and T-cell activation in human and animals [49][50][51]. All four candidates are also among the 52 high-scoring genes for QR lending further support for their importance in durable pathogen resistance (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…T-cell effector response (Christie et al 2012), thymocyte differentiation (Case et al 2011), graft-versus-host disease (Gatza et al 2011) or progression of experimental autoimmune encephalomyelitis (EAE) (Michalek et al 2011). Importantly, mitochondria and the cellular metabolic state are decisive for differentiation of T-cell subsets and development of memory and regulatory phenotypes (for further reading, please refer to (Gerriets and Rathmell 2012;Wang and Green 2012).…”
Section: The Enzymatic Sources Of the Oxidative Signalmentioning
confidence: 99%